2017
DOI: 10.3892/ol.2017.5786
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect and mechanism of exogenous mammalian sterile 20-like kinase 1 on the growth of human colorectal cancer

Abstract: The present study aimed to observe the inhibitory effect and preliminary mechanism of exogenous mammalian sterile 20-like kinase 1 (MST1) on the growth of colorectal cancer SW480 cells. The SW480 cells were randomly divided into the following groups: Control, empty enhanced green fluorescent protein (EGFP) plasmid (pEGFP-N1), MST1 EGFP plasmid (pEGFP-MST1), 20 µmol/l fluorouracil (5-FU) and pEGFP-MST1 + 5-FU. An MTS colorimetric assay was used to detect cell viability, Hoechst 33342 staining was used to observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…Gene therapy is an experimental strategy for colon cancer therapy with high efficiency [42]. STK4 acts as a tumor suppressor, and its overexpression inhibits tumor growth [21,43,44]. Our data also show that the change in STK4 levels negatively regulates β‐catenin‐mediated cell growth and cancer metastatic ability of colon cancer (Figs 2, 3A, and 5B).…”
Section: Discussionsupporting
confidence: 66%
“…Gene therapy is an experimental strategy for colon cancer therapy with high efficiency [42]. STK4 acts as a tumor suppressor, and its overexpression inhibits tumor growth [21,43,44]. Our data also show that the change in STK4 levels negatively regulates β‐catenin‐mediated cell growth and cancer metastatic ability of colon cancer (Figs 2, 3A, and 5B).…”
Section: Discussionsupporting
confidence: 66%
“…The Bcl2/Bax ratio is a classic indicator of apoptosis, and Bcl2/Bax plays an important role in the apoptosis of a variety of cells. [19]…”
Section: Discussionmentioning
confidence: 99%
“…Our recent studies [18,19] have found that regulating the MST1-Hippo signaling pathway can induce the apoptosis of lung cancer and colon cancer cells. Human mammalian sterile 20-like kinase 1 (MST1) is one of the core members of the Hippo pathway; the gene for MST1 is located on chromosome 20q11 and encodes a 59-K protein.…”
Section: Introductionmentioning
confidence: 99%
“…Several signalling pathways are responsible for apoptosis, including the gene coding for mammalian sterile 20-like kinase 1 (Mst1), an important mediator of cell death 8 , 9 . Mst1 has been largely studied in cancer biology, while little is known about its role in the pathophysiology of HF 10 12 . Mice with cardiac-specific overexpression of Mst1 have a phenotype consistent with HF due to dilated cardiomyopathy (DCM) 13 .…”
Section: Introductionmentioning
confidence: 99%